Determinants of the Use of Conventional Cigarettes in School Children in Yogyakarta City - Yuningrum , Hesti; Trisnowati , Heni (Universitas Negeri Semarang, 2024)
Background: The prevalence of child smokers in Indonesia continues to increase. The number of child smokers in Yogyakarta City also continues to increase. This study aims to describe the determinants of conventional cigarette use in school children in Yogyakarta City. Methods: The study used a quantitative method with a cross-sectional design. Data was collected through a direct survey of schools using the Kobo toolbox application. The sampling technique was proportional stratified random sampling. There were 582 samples from 3 State Junior High Schools and 4 Private Junior High Schools. Results: There was a correlation between knowledge and the use of conventional cigarettes (PR=4.22; CI=2.726-6.534; p <0.001), the affordability of cigarettes (PR=2.72; CI 95%=1.793-4.122; p <0.001), the availability of cigarettes (PR=2.60; CI 95%=1.738-3.893; p <0.001), family members' smoking behavior (PR=2.39; CI 95%=1.565-3.642; p <0.001) and peer smoking behavior (PR=7.79; CI 95%=4.707-12.920; p <0.001). The multivariate test results showed that the determinants most related to the use of conventional cigarettes in adolescents were peers (PR=9.36; CI 95%=5.138-17.038; p <0.001). Conclusion: The determinants of conventional cigarette use in children are peer smoking behavior, lack of knowledge related to conventional cigarettes and their impacts, smoking behavior of family members, cigarette addiction, and the availability of cigarettes. Suggestion: The results of research related to the determinants of smoking behavior can be used as advocacy material for policymakers to control cigarette consumption in school children.